Pengaruh Penggunaan Media Kantong Flanel terhadap Kemampuan Berhitung Penjumlahan Siswa Tunarungu 1 - Pradana, Richo Surya; Iriyanto, Tomas (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2015)
The purposes of research are to describe: (1) the ability of summation computation of a student with hearing impairment for 1st grade at baseline conditions (A1) and baseline conditions (A2), (2) the ability of summation computation of student with hearing impairment at intervention condition (B), and (3) the effect of flannel pocket media utilization toward the ability of summation computation for a student with hearing impairment in the 1st grade. The result was showed in the assessment of ability of summation computation for a student with hearing impairment in the baseline condition (A1) that was about 65% to the 75% and it had improvement to the intervention condition (B) to be 85% to 100%. as well as on baseline (A2) as control phase that the value was about 95% to the 100%.Tujuan penelitian : (1) mendeskripsikan kemampuan berhitung penjumlahan siswa tunarungu kelas 1 pada kondisi baseline (A1) dan baseline (A2); (2) mendeskripsikan kemampuan berhitung penjumlahan siswa tunarungu kelas 1 pada kondisi intervensi (B); (3) mendeskripsikan pengaruh penggunaan media kantong flanel terhadap kemampuan berhitung penjumlahan siswa tunarungu kelas 1. Hasil penelitian ini ditunjukkan pada penilaian kemampuan berhitung penjumlahan siswa tunarungu pada kondisi baseline (A1) berkisar 65% hingga 75% dan mengalami peningkatan pada kondisi intervensi (B) menjadi 85% hingga 100% serta pada kondisi baseline (A2) sebagai fase kontrol yang nilainya berkisar 95% hingga 100%.